Integrating Fundamental Movement Skills and Mathematics in Early Childhood: A Pilot Study - Catherine M. Capio; Sum Kwing Cheung; Serena S. W. Fung; Xinyun Hu (MDPI AG, 2024)
This project involved a co-design process involving researchers and kindergarten teachers to produce learning activities that integrated fundamental movement skills (FMS) and mathematics. We piloted the co-designed activities (i.e., motor-math program) in a local kindergarten and examined the effects on FMS proficiency, mathematics skills, and accrued physical activity (PA). The participants comprised pupils (N = 39) from two matched kindergarten classes, in which we compared the motor-math program with typical mathematics lessons. All participants wore pedometers to measure their number of steps during class, one day per week. FMS proficiency (i.e., locomotor, object control) and mathematics skills (numeracy, geometry, math problem solving) were measured before and after implementation. Significant improvements in locomotor and object control skills were found only in the pilot group (p < 0.001); there were no differences in the changes in mathematics skills between the pilot and comparison groups. During implementation days, the participants in the pilot group accrued significantly greater step counts (p < 0.001) than those in the comparison group. Participating in the motor-math program appears to have benefits associated with improvements in FMS proficiency and accrued PA time, suggesting a promising potential for integrated activities as a means of PA promotion in kindergarten settings. Future work that examines the effects of the integration of movement with mathematics should consider randomization, greater sample size, and a longer intervention period.